2001
DOI: 10.3168/jds.s0022-0302(01)74679-6
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Among Ambient Temperature, Day Length, and Milk Yield in Dairy Cows Under a Mediterranean Climate

Abstract: We examined the effect of calving month (CM) on the production of milk and milk protein by Israeli Holstein dairy cows located in the main climatic zone of Israel during their third and fourth lactations, and found it to be significant. Cows that calved in December produced the highest milk and milk protein yields, and those that calved in June produced the lowest, 92.8% of the maximum. The combined effect of the environmental average temperature and day length accounted for 0.96 of the variability in average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 19 publications
11
53
1
2
Order By: Relevance
“…Interestingly, it is the negative association between fat and proteins and spring found in the present study. Other authors (Barash et al, 2001;Aharoni et al, 2002) who analysed test-day records of different cow populations (Georgian and Israeli primiparous and Israeli multiparous) observed peaks in fat and protein concentration from October to January, an initial drop in spring and a significant decrease during summer in these parameters. The mechanism responsible for the decrease in fat and protein percentage in spring is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it is the negative association between fat and proteins and spring found in the present study. Other authors (Barash et al, 2001;Aharoni et al, 2002) who analysed test-day records of different cow populations (Georgian and Israeli primiparous and Israeli multiparous) observed peaks in fat and protein concentration from October to January, an initial drop in spring and a significant decrease during summer in these parameters. The mechanism responsible for the decrease in fat and protein percentage in spring is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a significant increase in the SCC during August and September. In a study carried out in Israel, cows that calved in December produced the highest milk and milk protein yields, and those that calved in June produced the lowest, 92.8% of the maximum (Barash et al, 2001). Information on THI milk fat and protein percentage and SCC relationships are scarce or lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These differences between different regions situated within close proximity and thus having similar macroclimates indicate that cow's milk production is also sensitive to regional climatic factors. Barash et al (2001) reported that average milk production was reduced by 0.38 kg/°C and protein by −0.01 kg/°C in Israeli Holstein dairy cows. Reiczigel et al (2009) observed that two of six indices were able to indicate milk production losses (1.5 to 2 litres per cow per day) due to heat stress.…”
Section: Evaluation Of Thi Bomentioning
confidence: 99%
“…In contrast, Berman et al (1985) measured upper critical ambient temperatures from 258C to 268C in Israel. The antagonistic effect of heat (20.38 kg milk/8C and 20.01 kg protein/8C) and photoperiod (1.2 kg milk and 0.02 kg protein/1 h longer daily light) has been calculated by Barash et al (2001) in Israeli Holstein cows. The estimates of Berman (2005) on Israeli Holstein cows showed that higher-yielding dairy cows are more sensitive to heat stress.…”
Section: Effects Of Hyperthermia On Dna Integrity and Embryonic Develmentioning
confidence: 99%